KEANEKARAGAMAN TUMBUHAN OBAT DALAM KAWASAN HUTAN SEKUNDER AREAL IUPHHK PT. KALIMANTAN SATYA KENCANA KABUPATEN MELAWI - Mustika, Mega; Herawatiningsih, Ratna; Latifah, Siti (Universitas Tanjungpura, 2014)
Forest in the area of IUPHHK (Timber Forest Product Utilization Permit) PT. Kalimantan Satya Kencana is one of the forest where located in the Melawi district that has high enough of flora diversity. The medicinal plants that is part of the biological germplasm. The purpose of this study this to determine the diversity of medicinal plants in secondary forest (slash ex 2008) at the area of IUPHHK PT. Kalimantan Satya Kencana Melawi District. This study used quadrant method with multiple plots. Purposive sampling it has chosen by observation in according to the local communities most numerous types of medical plants. There was 71 medicinal plants outside the plots founded in the observations. The dominance index (C) of the tree level = 0.108. Tree level (C) of = 0.238. Saplings (C) of = 0.83. Plant Nursery and Lower level (C) of = 0.042. Species Diversity Index (H) to the level of the tree = 1.017, for the level of the pole (H) at = 0.629, sapling level (H) at = 1.084 and lower levels, and Plant Nursery (H) at = 1.455. Wealth index type (d) at tree level of = 6.695. Pole at = 2.590 level. Of = 10,204 saplings, seedlings and undergrowth for 20,325. Abundance index type (e) at the tree level of = 0.937. Tree level index (e) of = 0.924. Saplings (e) = 0.968 for seedlings and understory plants (e) of = 0.887. can be seen that the dominance index (C) which is highest at the Stake level, the value of Species Diversity Index (H) Rate of Seedling and Understory Plants and Index Property Type (d) which is highest at the level of the Seedling Â and Understory Plants, while the highest for the Abundance Index type (e) find at tree level. Keywords: Medicinal plants diversity, secondary forest, timber forest product utilization